PENGEMBANGAN WISATA KULINDES (KULINER PEDESAAN) BERBASIS PANGAN LOKAL DI DESA PANGAUBAN KECAMATAN BATUJAJAR KABUPATEN BANDUNG BARAT - Ellis Endang Nikmawati (Lentera Karya Edukasi, 2021)
Abstract: The Pangauban Village government program is still physically oriented and there is still a small budget for human development, especially women's empowerment. In general, housewives are limited to processing food for the family. Pangauban village has the potential for culinary tourism but has not yet developed. Agricultural products and associations as local food have not been processed and developed into superior food products by Kulindes. Pangauban Village has a large number of farmer groups and PKK women who are members of the Village women's empowerment forum but do not yet have special expertise in the culinary field. The main problem that needs to be solved with this service activity is the effort to grow the ability to process, serve, and package local food-based culinary mothers in the service village of Pangauban Village which is still conventional. Community service activities for developing Kulindes tourism based on local food in Pangauban Village are as follows: (1). Knowing the utilization of local food potential with the village culinary tourism program; (2). Knowing the paradigm of the local food-based culinary tourism model for PKK women; (3). Knowing the creative entrepreneurship model that is suitable for village youth youth; (4). Initiating a creative local food-based village culinary tourism model for posyandu cadres.Abstrak: Program pemerintah Desa Pangauban masih berorientasi pisik dan masih kecil anggaran untuk peningkatan manusia terutama pemberdayaan perempuan. Pada umumnya ibu-ibu rumah tangga hanya terbatas mengolah makanan untuk keluarga. Desa Pangauban memiliki potensi wisata kuliner namun belum berkembang.Hasil pertanian dan perikatan sebagai pangan local belum banyak diolah dan dikembangkan menjadi produk pangan unggulan oleh-oleh Kulindes.  Desa Pangauban memiliki kelompok usaha tani dan ibu-ibu PKK  yang tergabung dalam wadah pemberdayaan perempuan Desa dengan jumlah yang cukup besar namun belum memiliki keahlian khusus di bidang Boga. Permasalahan utama yang perlu dibantu pemecahannya dengan kegiatan pengabdian ini adalah upaya menumbuhkan kemampuan pengolahan, penyajian, dan pengkemasan kuliner berbasis pangan lokal  para ibu di desa layanan Desa Pangauban yang masih konvensional. Kegiatan pengabdian kepada masyarakat pengembangan wisata Kulindes berbasis pangan lokal di Desa Pangauban adalah sebagai berikut: (1). Mengetahui pemanfaatan potensi pangan lokal dengan Program wisata kuliner desa; (2). Mengetahui paradigma model wisata kuliner berbasis pangan lokal ibu-ibu PKK; (3). Mengetahui model wirausaha kreatif yang cocok untuk pemuda karang taruna desa; (4). Menginisiasi model wisata kuliner desa berbasis pangan lokal kratif bagi ibu-ibu PKK.